2020
DOI: 10.1364/oe.393491
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive temperature sensing probes based on liquid cladding elliptical micro/nanofibers

et al.

Abstract: A highly sensitive temperature probe based on a liquid cladding elliptical micro/nanofiber is proposed, which exploits a fiber loop mirror with an output port probe for remote and highly-sensitive measurements based on evanescent field coupling. The thermo-optical effective liquid cladding avoids the influence of other environmental parameters (except for temperature), while protecting the micro/nanofibers from external disturbance and contamination. This renders the sensing probe only sensitive to temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other hand, conventional optical fiber-based SPR sensors have progressed a lot due to their high resolution, a miniaturized structure, and reliability in remote sensing applications [7,8]. But these types of fibers are single mode or multimode fibers which consist of a core and cladding section; therefore, the external part of the fiber is chemically or physically isolated to reveal the core region to enhance the linking among the surface plasmon polariton (SPP) mode and the core mode [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, conventional optical fiber-based SPR sensors have progressed a lot due to their high resolution, a miniaturized structure, and reliability in remote sensing applications [7,8]. But these types of fibers are single mode or multimode fibers which consist of a core and cladding section; therefore, the external part of the fiber is chemically or physically isolated to reveal the core region to enhance the linking among the surface plasmon polariton (SPP) mode and the core mode [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, D-shaped fiber structures are reported, in which half part of the cladding section is polished, which allows a stronger interaction between the optical mode and the target analytes [14,15]. Wang et al demonstrated the temperature sensor based on helical core fiber which is polished as a D-type fiber coated with the layer of gold [16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to fiber grating based temperature sensors, fiber interferometer based temperature sensors are much more desirable sensors and have gradually become the most widely used optical fiber temperature sensors for their simple structure and high sensitivity. The fiber interferometers employed to construct temperature sensors mainly contain Fabry-Perot interference (FPI) [15][16][17][18], Michelson interferometer (MI) [19,20], Mach-Zehnder interferometer (MZI) [21][22][23] and Sagnac interferometer (SI) [24][25][26][27][28][29][30], which are fabricated by using different kinds of fibers including thin core fiber [15], single mode fiber [19][20][21][22], microfiber [23,30], polarization maintain fiber [24][25][26]28], photonic crystal fiber [27,29] and so on. Among the above mentioned fiber interferometers, a very high temperature sensitivity of −16.38 nm/°C has been achieved with an isopropanol cladding elliptical microfiber based SI [30].…”
Section: Introductionmentioning
confidence: 99%